Uncovers The Dynamics of The State Civil Apparatus in Indonesia: Implications for Governance and Institutional Quality - Priyo Budi Santoso (Public Policy and Management Inquiry, 2025)
The dynamics of the State Civil Apparatus in Indonesia delivered special attention to the governance and institutional quality issues. Admittedly, these dynamics displayed the process of marginalization in political-administration, which affects the State Civil Apparatus in terms of professionalism, integrity, and neutrality, with the efforts to scale down the regulation from the central government intervention. Next, this reveals a gap in institutional fallout with other connections, such as deconstruction by state-led oversight mechanisms, and the long-term effects of governance and institutional quality. Through qualitative descriptive methods and an argumentative review, it was found that the implications of the marginalization process for the governance and institutional quality distort the fundamental principles, which are based on the tools of political power, and display inefficiency, misuse of power, and corruption while reducing public trust in government institutions. Interestingly, the urgency of the executive and legislative commitment from the dynamic only prioritizes the interests of groups behind the political agenda designed to influence the State Civil Apparatus’ performance. Consequently, the study implies that governance and institutional quality are the connecting elements that grant the function of government activities through the State Civil Apparatus, and the researcher’s perspective provides the information on how political interference, when unchecked, affects reform momentum and administrative functioning.